2002
DOI: 10.1002/neu.10023
|View full text |Cite
|
Sign up to set email alerts
|

Rare and spatially segregated release sites mediate a synaptic interaction between two identified network neurons

Abstract: Laser-scanning confocal microscopy (LSCM), electron microcopy (EM), and cellular electrophysiology were used in combination to study the structural basis of an inhibitory synapse between two identified neurons of the same network. To achieve this, we examined the chemical inhibitory synapse between identified neurons belonging to the lobster (Homarus gammarus) pyloric network: the pyloric dilator (PD) and the lateral pyloric (LP) neurons. In order to visualize simultaneously these two neurons, we used intrasom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
(56 reference statements)
2
7
0
Order By: Relevance
“…2B). This is consistent with findings in H. gammarus that show extended branching and synaptic contacts of STG neurons into the stn (Cabirol‐Pol et al,2002). Occasionally, we found isolated regions of labeling in the stn, 35 mm anterior to the ganglion (insert in Fig.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…2B). This is consistent with findings in H. gammarus that show extended branching and synaptic contacts of STG neurons into the stn (Cabirol‐Pol et al,2002). Occasionally, we found isolated regions of labeling in the stn, 35 mm anterior to the ganglion (insert in Fig.…”
Section: Resultssupporting
confidence: 92%
“…Associated with the somata, as well as distributed throughout the neuropil, were brightly labeled small ellipsoids (gray arrow in inset) that we interpret as either glia cells or glia cell nuclei (French et al,2002). As in P. interruptus (King,1976a), C. borealis (Kilman and Marder,1996), and H. gammarus (Cabirol‐Pol et al,2002), the core of the neuropil in H. americanus contains mostly larger branches (white arrows in middle and lower panel), whereas fine branches make up the peripheral layer of the neuropil (black arrows). Synapsin‐like IR was restricted to the fine neuropil.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It is interesting that the number of individual candidate contact sites between AGR and putative synaptic partners was generally very low, ranging from one to three. In agreement with this, it has been suggested that only few sites of synaptic contact exist between two identified motor neurons of the pyloric network in the European lobster [50]. This pattern of sparse synaptic contact sites supports the idea that dendritic integration in STG neurons is not evenly distributed across the neuropil but rather compartmentalized, as suggested previously in this system by analysis of motor neuron morphology and sub-cellular receptor distribution [15,16,51].…”
Section: Discussionsupporting
confidence: 85%